2018
DOI: 10.1002/dmrr.3022
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA/ROCK pathway mediates high glucose‐induced cardiomyocyte apoptosis via oxidative stress, JNK, and p38MAPK pathways

Abstract: The RhoA/ROCK pathway mediates HG-induced cardiomyocyte apoptosis via oxidative stress and activation of p38MAPK and JNK in neonatal rats in vitro. Fasudil effectively ameliorates HG-induced cardiomyocyte apoptosis by suppressing oxidative stress and the p38MAPK and JNK pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…ONC is known to stimulate the production of reactive oxygen species and activates the stress-responsive signaling pathways such as the apoptosis signal-regulating kinase 1 (ASK1)-p38 pathway, and intraocular injection of a p38 inhibitor partially prevents ONC-induced RGC death 1,16 . Our results are consistent with the previous reports that various ROCK inhibitors suppress stress-activated MAPK family members including p38 17,18 . One may think that topical administration in mice often allows the drug to reach the retina much easier than larger animals, and argue that the current results may not be meaningful in human patients.…”
Section: Discussionsupporting
confidence: 93%
“…ONC is known to stimulate the production of reactive oxygen species and activates the stress-responsive signaling pathways such as the apoptosis signal-regulating kinase 1 (ASK1)-p38 pathway, and intraocular injection of a p38 inhibitor partially prevents ONC-induced RGC death 1,16 . Our results are consistent with the previous reports that various ROCK inhibitors suppress stress-activated MAPK family members including p38 17,18 . One may think that topical administration in mice often allows the drug to reach the retina much easier than larger animals, and argue that the current results may not be meaningful in human patients.…”
Section: Discussionsupporting
confidence: 93%
“…In our work, propranolol triggered a significant increase in ROS generation by flow cytometry analysis. Growing evidence [39] has demonstrated that various oxidative stress signals also activated JNK pathway to promote cell apoptosis and autophagy. Western blot results showed that propranolol significantly enhanced the expression of JNK phosphorylation both in SKOV-3 and A2780 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, propranolol triggered a signi cant increase in ROS generation by ow cytometry analysis. Growing evidence [38] have demonstrated that various oxidative stress signals also activated JNK pathway to promote cell apoptosis and autophagy. Western blot results showed that propranolol signi cantly enhanced the expression of JNK phosphorylation both in SKOV-3 and A2780 cells.…”
Section: Discussionmentioning
confidence: 99%